Towards a Disentangling the Anatomy of Human Society: A Self- Clarification - Gueco, Reynaldo (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 1 (2000): Economies in Flux, 2009)
Homo sapiens, unlike no other species save for posthumously popular dinosaurs, has dominated all other living organisms mainly because of its ability to change its very nature as a species both consciously and deliberately. As a species, Homo sapiens excelled in the art of tool making, specifically, making tools out of members of the species. The most creative toolmakers became the dominant class, the class that dictates cultural and political behavior. The most common tools have evolved into the proletariat. In the last 10,000 years of dominance, Homo sapiens have successfully defined and redefined human and social relations, creating three spheres of human society: political society (embodied in the capitalist nation-state), class society (embodied in the slave, feudal and capitalist property relations), and natural society (embodied in the ancient, Asiatic, slave, feudal and capitalist techniques of producing wealth). So far, capitalism has successfully kept the Manifesto-predicted communist revolution at bay and the proletariat at its dehumanized state. The next revolution, unleashed by the errors and excesses of economic globalization, will not succeed with the mere collapse of the nation-state and the triumph of the proletariat. All three spheres must undergo changes and become arenas of social revolution to end the total hegemony of capital in human society. In this dreamt-for transformed society, the application of price form and capital form on Homo sapiens is eradicated.